Extraction and identification of anti-oxidants, anti-inflammatory, anti-cancerous and cosmetic compounds from the mucus of a slug Laevicaulisalte - P.S , Suja; C , Nija.; M, Navinchandran. (Journal of Neonatal Surgery, 2024)
India is the birthplace of new indigenous medical systems like Siddha, Ayurveda, and Unani. Natural materials have been a major source of pharmaceuticals since ancient times; currently, about half of the most potent medications originate from natural sources. Ancient Greeks were interested in snail and slug mucus trails because it had anti-inflammatory and antioxidant properties (Ekin et al., 2018). In Kanyakumari District, the land slug Laevicaulisalte is frequently observed. Its mucus is a stretchy, sticky substance that has lubricating and adhesive qualities. The bioactive elements of slug crude mucus have been evaluated by GC-MS analysis; these compounds exhibit antibacterial, anti-oxidant, anti-inflammatory, and anti-cancer activities. Five antioxidant, four anti-inflammatory, and three anti-cancerous compounds were isolated. Tetrapentacontane (39.510), 1-Heptacosanol (39.414), and 2-hydroxyl-1-(hydroxymethyl) ethyl ester (41.227) all have long retention times. It is well recognized that the chemicals found have therapeutic benefits